Diet of the beach lizard Microlophus peruvianus (Reptilia : Tropiduridae) in the Santo Domingo beach, Ica, Peru - Quispitúpac, Eliana (2008)
Even the beach lizard Microlophus peruvianus is one of the most conspicuous saurian species in the Peruvian desert, however there is almost none information about its diet. Here we reported important evident about the diet differences of both M. peruvianus adult and juvenile in Santo Domingo beach, Ica, which could be reduced the intraspecific competition between them.